Digitization of Biodiversity Collections and a Lighting Cabinet Design - Hakan Çalışkan; Hatice Kübra Yalçın (Turkish Journal of Bioscience and Collections)
Objective: There are millions of specimens in biodiversity collections and museums. The conversion of these specimens in collections to digital data started in the last quarter century and has increased rapidly. This process has caused museums to create digital specimens. In this study, it is aimed to simplify digital photography and to standardize the creation of data sets in digitizing the existing biodiversity collections in our country and to present them to open access by combining them with different collections. Materials and Methods: In the study, the methods used for obtaining digital images of vertebrate and invertebrate animals in the collection of the ESOGÜ Zoology Museum and creating data sets are shared. A lighting cabinet consisting of 60 × 60 cm 40 W LED panels was designed and used to take the digital images of the samples. Results: A registration code of six letters and six numbers, which will be used to create inventories of biodiversity samples, and three different sample data labels for the exhibited samples were designed in the study. A naming rule has been established for archiving all digital images in a digital environment. Conclusion: Information on using the designed lighting cabinet in different animal museum specimens is provided and the results are shared.